Impact of Energy Consumption and Carbon Dioxide Emissions on Economic Growth: Cointegrated Panel Data in 79 Countries Grouped by Income Level - Salazar-NÃºÃ±ez, HÃ©ctor F.; Venegas-MartÃnez, Francisco; Tinoco-ZermeÃ±o, Miguel Ã (International Journal of Energy Economics and Policy, 2020)
This paper investigates the existence of causal relationships among primary energy consumption per capita (PEC), carbon dioxide per capita (CO2) and gross domestic product per capita (GDP) in 79 countries grouped by income level for the 1980-2014 period. The countries are classified into high (HIC), upper-middle (UMIC), lower-middle (LMIC), and low (LIC) average per capita income. We apply a model of cointegrated panel data and an error correction mechanism. The estimation is carried out with fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS). For the HIC and UMIC groups, there is, in general, a positive relationship between PEC and GDP, and a negative one between GDP and PEC given that they develop new technologies to reduce CO2 emissions. For the LMIC and LIC groups there are mixed results. For instance, the LIC group accepts the null hypothesis in 26% of the cases with FMOLS and 42% with the DOLS. The Granger causality test suggests that for the HIC, UMIC and LMIC groups the variable GDP has a bidirectional relationship with PEC and CO2 in the short and long runs, a bidirectional causal relationship between PEC and CO2 in the long run, and unidirectional from PEC to Co2 in the short run. For the LIC group, PEC and CO2 show a bidirectional relationship, but unidirectional from PEC to CO2 in the short term. We also only detected a bidirectional relationship between CO2 and GDP in the short term for the LIC group. Keywords: Energy consumption, carbon dioxide emission, economic growth, country income classification, time series analysis with panel data. JEL Classifications: O13, H54, O47, C31, C33, L70. DOI: https://doi.org/10.32479/ijeep.8783